Quenching of antihydrogen gravitational states by surface charges. (5th October 2016) - Voronin, A Yu; Kupriyanova, E A; Lambrecht, A; Nesvizhevsky, V V; Reynaud, S
Abstract: We study the effect of the quenching of antihydrogen quantum states near the surface of a material in the Earth's gravitational field by local charges randomly distributed along a mirror surface. The quenching reduces the probability of quantum reflection because of the additional atom–charge interaction, and thus the nonadiabatic transitions to excited gravitational states. Our approach is suitable when accounting for quenching caused by any kind of additional interaction with a characteristic range much smaller than the typical gravitational state wavelength.